Analisis Peran Bank Perekonomian Rakyat Syariah (BPRS) dalam Pengembangan Usaha Mikro: Studi Kasus: PT. BPRS Taeh Baruah Kab. Lima Puluh Kota - Tini Hayatul Huri; Rini Elvira (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
Bank Perekonomian Rakyat Syariah (BPRS) is a financial institution that operates according to sharia principles, focusing on providing financial services to the community, especially micro and medium-sized businesses. The main problem in this thesis is that out of  a total of 1.200 mcro-enterprneurs, only 485 have received financing from BPRS Taeh Baruah. This is because they do not yet have a business licence, so mcro-enterpreneurs prefer to borrow from non-formal financing institutions such as the PNM Mekaar program or farmer groups. This study aims to analyze the role of Bank Perekonomian Rakyat Syariah (BPRS) Taeh Baruah in micro-enterprise development. The research method used is a qualitative method with a descriptive approach. Data collection techniques used are through interviews and literature studies. Informants in this study consisted of 11 BPRS financing staff and 49 micro-enterprise customers at BPRS Taeh Baruah. The research results show that BPRS Taeh Baruah plays a significant role in supporting the development of micro-enterprises through sharia-based financing, particularly by using the murabahah contract, which is the most widely used by customers. Furthermore, BPRS Taeh Baruah also plays a role in increasing sharia financial inclusion by providing savings and financing services, conducting regular literacy and education related to sharia finance, and implementing flexible service strategies such as savings and financing pickup services, the use of mobile banking service. The Taeh Baruah BPRS also play a role in improving community welfare through financing programs provided to micro-enterpreneurs for working capital, enabling their business to grow. The additional capital provided by the BPRS ensures the availability of materials and eqipment for their businesses, thus contibuting to economic stability.